The Influence of the Investment Opporttunity Set (IOS), Profitability, Investment Decisions, Dividend Policy, and Corporate Social Responsibility (CSR) on the Value of Manufacturing Companies Listed on the Indonesia Stock Exchange 2015-2019 - Heru Suwasono (International Journal of Seocology, 2021)
This study aims to determine the effect of investment opportunity set (IOS), profitability, investment decisions, dividend policy, and coporate social responsibility (CSR) have a significant effect on company value in manufacturing companies on the Indonesia Stock Exchange 2015-2019. The sample in this study used purposive sampling in order to obtain 33 sample companies from 187 population of manufacturing companies listed on the Indonesia Stock Exchange, with 165 observations of financial statements (33 companies x 5 years of financial statement observations). The dependent variable in this study is company value. While the independent variables in this study, are IOS, profitability, investment decisions, dividend policy, and CSR. The data analysis method used is a type of multiple regression test to test the relationship between the independent and dependent variables. The results of this research hypothesis testing prove that IOS, profitability, dividend policy, and CSR have a significant effect on company value while investment decisions do not have a significant effect on company value in manufacturing companies on the Indonesia Stock Exchange in 2015-2019. The F test shows that Fcount is 938.069 with a significant 0.000 indicating that IOS, profitability, investment decisions, dividend policy, and CSR simultaneously affect company value. The coefficient of determination (R2) IOS, profitability, investment decisions, dividend policy, and CSR have an influence on company value of 96.7% while the remaining 3.3% is influenced by other variables not examined. Based on the results of the tests conducted, it can be recommended to use proxies for IOS, profitability, dividend policy, and CSR in assessing company value, because these proxies have a significant effect on company value.